Aerodynamic and thermal field development of cooled transonic HP NGV - Amend, J; Lubbock, R; Ornano, F; Chowdhury, N; Povey, T (ASME International, 2023)
In this study we present detailed aerodynamic and thermal field measurements downstream of an annular cascade of fully-cooled nozzle guide vanes (NGVs). The experiments were conducted in the Engine Component Aerothermal (ECAT) facility at the University of Oxford, at engine-matched conditions of Reynolds number and Mach number, and high turbulence intensity. The experimental data are unusually high-fidelity and allow for detailed comparison with modern computational fluids dynamics (CFD) methods. We compare the experimental data to simulations of fully-featured geometry (resolved internal geometry and film cooling holes). We analyze distributions of whirl angle, kinetic energy loss, and non-dimensional temperature at three axial planes downstream of the NGVs. The aerodynamic and thermal wakes are also characterized in terms of their spreading and decay rates. The analysis is deepened with detailed comparison to a previous data-set for a different design of heavily-cooled NGV. The analysis is a useful reference point for assessing the accuracy of the current state-of-the-art numerical methods used in the engine design process.